CONSTRUCTING THE AFFORDABILITY INDEX OF ICTS AND INTERNET SERVICES IN THAILAND AND SELECTED ASIAN COUNTRIES - Mana Luksamee Arunothai (PEOPLE: International Journal of Social Sciences, 2025)
The primary objective of this research is to formulate an index designed to quantify the affordability index of ICTs and internet services in Thailand in relation to 8 chosen countries: Singapore, Malaysia, Indonesia, the Philippines, Vietnam, China, Japan, and South Korea. The goal is to undertake a comparative analysis of strengths and weaknesses, and to proffer policy recommendations to bolster the affordability and reduce the problem of the digital divide. The index is a composite index having 2 main factors: (1) the price of access to ICTs (a 50% weighting) with 4 sub-factors – the mobile-cellular basket as share of GNI per capita; the mobile-cellular sub-basket (in USD); the mobile-cellular sub-basket (in PPP); and tax rates on mobile services, and (2) the price of access to the internet (a 50% weighting) with 5 sub-factors – the fixed-broadband basket as share of GNI per capita; the fixed-broadband sub-basket (in USD); the fixed-broadband sub-basket (in PPP); tax rates on fixed broadband services; and broadband internet speeds. The findings of the study disclose that in the year 2023, the affordability index in Thailand was 0.973 which was lower than an average of 8 benchmark countries of 0.979 (Singapore 0.998, China 0.994, South Korea 0.994, Japan 0.992, Malaysia 0.990, Vietnam 0.986, Indonesia 0.974, and the Philippines 0.966, respectively). The index ranges from 0 to 1 with higher numbers indicating higher affordability. The competitive weaknesses of Thailand are concentrated in the mobile-cellular sub-basket (in both USD and PPP), tax rates on mobile services, and fixed-broadband sub-basket (in PPP).Thailand’s competitive strengths, on the other hand, are predominantly located within the fixed-broadband basket as share of GNI per capita and broadband internet speeds. The future scope of the study should consider other indicators of digital divide such as communication infrastructures, computer availability, availability of alternative access through TVs or mobile phones, and internet access.